GAMBARAN BRAND IDENTIFICATION DAN BRAND LOVES PADA PENGGUNA FORUM JUAL BELI KASKUS DI KOTA BANDUNG - Maulana, Fajar Gumelar; Wibowo, Lili Adi; Widjajanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - To find out the description of the level of brand identification and brand loves in kaskus buyer-seller forum user Bandung City. Design/methodology/approach - The design of this study is cross sectional method. This research uses descriptive approach with explanatory survey method. A total of 107 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique by using frequency distribution.Findings - The result showed that brand identification is in good enough category, while brand loves is in medium category. Â Originality / value - The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study